d-allulose provides cardioprotective effect by attenuating cardiac mitochondrial dysfunction in obesity-induced insulin-resistant rats - Wanpitak Pongkan (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: Obesity-induced insulin resistant is associated with cardiovascular diseases via impairing cardiac mitochondria. Recently, d-allulose could protect β-islets and improve insulin resistance. However, the effects of d-allulose on the heart and cardiac mitochondrial function under obesity-induced insulin-resistant condition has not been investigated. In this study, we aimed to investigate the effects of d-allulose on metabolic parameters, cardiac function, heart rate variability (HRV), cardiac mitochondrial function, and apoptosis in the heart of obesity-induced insulin-resistant rats induced by chronic high fat diet consumption. Methods: Male Wistar rats (n = 24) received a normal fat diet (ND) or high fat diet (HFD) for 12 weeks. Then, HFD group was randomly divided into three subgroups to receive (1) HFD with distilled water, (2) HFD with 3% D-allulose 1.9 g/ kg·BW/ day (HFR), and (3) HFD with metformin 300 mg/kg·BW/ day (HFM) by diluted in drinking water daily for 12 weeks. At week 24, proposed study parameters were investigated. Results: Chronic HFD consumption induced obesity-induced insulin resistant in rats and high fat diet impaired cardiac function and HRV. HFR rats had improved insulin sensitivity as indicated by decreasing HOMA index, plasma insulin, whereas HFM decreased body weight, visceral fat, plasma cholesterol, and plasma LDL. HFR and HFM provided similar efficacy in improving HRV and attenuating cardiac mitochondrial dysfunction, leading to improved cardiac function. Conclusions: Even though this is the first investigation of the d-allulose impact on the heart with a relatively small sample size, it clearly demonstrated a beneficial effect on the heart. d-allulose exerted a therapeutic effect on metabolic parameters except for body weight and lipid profiles and provided cardioprotective effects similar to metformin via attenuating cardiac mitochondrial function in obesity-induced insulin-resistant rats.